Deuterium temperature, drift velocity, and density measurements in non-Maxwellian plasmas at ASDEX Upgrade. (1st February 2018) - Salewski, M.; Geiger, B.; Jacobsen, A.S.; Abramovic, I.; Korsholm, S.B.; Leipold, F.; Madsen, B.; Madsen, J.; McDermott, R.M.; Moseev, D.; Nielsen, S.K.; Nocente, M.; et al.
Abstract: We measure the deuterium density, the parallel drift velocity, and parallel and perpendicular temperatures ( T ∥, T ⊥ ) in non-Maxwellian plasmas at ASDEX Upgrade. This is done by taking moments of the ion velocity distribution function measured by tomographic inversion of five simultaneously acquired spectra of D α -light. Alternatively, we fit the spectra using a bi-Maxwellian distribution function. The measured kinetic temperatures ( T ∥ = 9 keV, T ⊥ = 11 keV) reveal the anisotropy of the plasma and are substantially higher than the measured boron temperature (7 keV). The Maxwellian deuterium temperature computed with TRANSP (6 keV) is not uniquely measurable due to the fast ions. Nevertheless, simulated kinetic temperatures accounting for fast ions based on TRANSP ( T ∥ = 8.3 keV, T ⊥ = 10.4 keV) are in excellent agreement with the measurements. Similarly, the Maxwellian deuterium drift velocity computed with TRANSP (300 km s −1 ) is not uniquely measurable, but the simulated kinetic drift velocity accounting for fast ions agrees with the measurements (400 km s −1 ) and is substantially larger than the measured boron drift velocity (270 km s −1 ). We further find that ion cyclotron resonance heating elevates T ∥ and T ⊥ each by 2 keV without evidence for preferential heating in the D α spectra. Lastly, we derive an expression for the 1D projection of an arbitrarily drifting bi-Maxwellian onto a diagnostic line-of-sight.